Comparative study of esophagectomy, endoscopic therapy, and radiotherapy for cT1N0M0 esophageal cancer in elderly patients: A SEER database analysis. Issue 7 (14th June 2019) - Qin, Jianjun; Peng, Yinjie; Chen, Weipeng; Ma, Haibo; Zheng, Yan; Li, Yin; Wang, Jun
Abstract : Background: The number of patients diagnosed with early stage disease (T1a or T1b) has been increasing. This study was conducted to investigate the effect of esophagectomy (ES), endoscopic therapy (ET), and radiotherapy (RT) on long‐term survival in elderly patients with cT1N0M0 esophageal cancer. Methods: We searched the Surveillance, Epidemiology, and End Results (SEER) database to identify the records of elderly patients (≥ 75 years) with cT1N0M0 esophageal cancer between 2004 and 2014. Patient demographics and esophageal cancer parameters were compared among ES, ET, and RT groups. The Kaplan–Meier method and Cox proportional hazard modeling were used to compare long‐term survival. Results: Data from 954 esophageal cancer patients (ES: n = 196; ET: n = 224; RT: n = 534) were identified. Multivariate Cox regression analysis showed that five‐year survival in the ET and ES groups was significantly higher than in the RT group. After propensity score matching, we found no difference in five‐year survival between ES and ET. Conclusion: Using SEER data, we identified a significant survival advantage with the use of ES and ET compared to RT in patients with cT1N0M0 esophageal cancer aged > 75 years, while the long‐term survival of patients after ET and ES was not significantly different.